FLOTAC for diagnosis of endo-parasites in pet squirrels in southern Italy - d’Ovidio, D.; Rinaldi, L.; Ianniello, D.; Donnelly, T.M.; Pepe, P.; Capasso, M.; Cringoli, G. (Veterinary parasitology, 2014)
The present study investigated the occurrence of endoparasites in pet squirrels in southern Italy. Fresh fecal samples were collected from 50 asymptomatic pet squirrels belonging to five different species (Callosciurus finlaysonii, n=6, C. prevosti, n=6; Tamias striatus, n=26, T. sibiricus, n=10; Sciurus carolinensis, n=2) housed both in pet shops and/or in private residences. All fecal samples were processed using the FLOTAC pellet technique to identify and count helminth eggs/larvae and protozoan cysts/oocysts. In addition, to detect Cryptosporidium spp. and Giardia spp. the samples were analyzed by the Remel Xpect(®) immunoassay. Helminth eggs were detected in 9 out of 50 squirrels. Specifically, eggs of Dicrocoelium dendriticum were found in 5 squirrels (C. finlaysonii, n=2; C. prevosti, n=2; T. striatus, n=1); eggs of the pinworm Syphacia spp. in 3 squirrels (C. prevosti, n=2; T. striatus, n=1); and eggs of gastrointestinal nematoda (Nippostrongylus-like) were found in 1 subject (C. prevosti). Finally, two squirrels (C. prevosti) had multiple parasitic infections with D. dendriticum and Capillaria hepatica, and with D. dendriticum and Strongyloides spp., respectively. None of the samples were positive for Cryptosporidium spp. or Giardia spp. or any other protozoa (e.g. Eimeria). To the authors' knowledge, this is the first report of a D. dendriticum natural infection in pet rodents.